2011
DOI: 10.19030/jier.v7i2.4246
|View full text |Cite
|
Sign up to set email alerts
|

University Students Attitudes: Croatia Versus Turkey

Abstract: We surveyed Croatian and Turkish business school students, from universities emphasizing globalization, to analyze whether consideration for travel to the USA is affected by attitude toward their own country and the USA The results from comparing and contrasting differences between these countries and differences between males and females in each country - and their counterparts in the other country - may also give an outlook to future business relationships between the USA and these countries. Based on a t-te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…Additionally, the focus on the younger population indicates the opposite findings. In accordance with Schnurr et al (2011), Croatian students, attending the Faculty of Economics and Business at the University of Zagreb generally expressed positive attitudes regarding the future. More recent research (Tipurić et al, 2013) has shown that students' attitudes toward resolving business crisis situation differ significantly: from facing the challenges and using active strategies (students of the Faculty of Political Science, University of Zagreb) to using passive approach imbued with caution (students of the Faculty of Economics and Business, University of Zagreb).…”
Section: Introductionmentioning
confidence: 88%
“…Additionally, the focus on the younger population indicates the opposite findings. In accordance with Schnurr et al (2011), Croatian students, attending the Faculty of Economics and Business at the University of Zagreb generally expressed positive attitudes regarding the future. More recent research (Tipurić et al, 2013) has shown that students' attitudes toward resolving business crisis situation differ significantly: from facing the challenges and using active strategies (students of the Faculty of Political Science, University of Zagreb) to using passive approach imbued with caution (students of the Faculty of Economics and Business, University of Zagreb).…”
Section: Introductionmentioning
confidence: 88%